2005
DOI: 10.1002/humu.20212
|View full text |Cite
|
Sign up to set email alerts
|

Microdeletions and microinsertions causing human genetic disease: common mechanisms of mutagenesis and the role of local DNA sequence complexity

Abstract: In the Human Gene Mutation Database (www.hgmd.org), microdeletions and microinsertions causing inherited disease (both defined as involving < or = 20 bp of DNA) account for 8,399 (17%) and 3,345 (7%) logged mutations, in 940 and 668 genes, respectively. A positive correlation was noted between the microdeletion and microinsertion frequencies for 564 genes for which both microdeletions and microinsertions are reported in HGMD, consistent with the view that the propensity of a given gene/sequence to undergo micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
166
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 139 publications
(182 citation statements)
references
References 35 publications
12
166
4
Order By: Relevance
“…Small deletions (95/135, 70%) were 2.3 times more common than small insertions (40/135, 27%). These proportions are comparable with those given in a comprehensive review of microdeletions and microinsertions deposited in the Human Gene Mutation Database (Ball et al, 2005), where deletions are reported to be approximately 2.5 times more frequent than insertions. The authors suggest that a biased mechanism in the mutational process generating these alterations accounts for the greater probability of small deletions than small insertions.…”
Section: Small Deletions and Small Insertions: Frameshift Mutations Asupporting
confidence: 83%
See 1 more Smart Citation
“…Small deletions (95/135, 70%) were 2.3 times more common than small insertions (40/135, 27%). These proportions are comparable with those given in a comprehensive review of microdeletions and microinsertions deposited in the Human Gene Mutation Database (Ball et al, 2005), where deletions are reported to be approximately 2.5 times more frequent than insertions. The authors suggest that a biased mechanism in the mutational process generating these alterations accounts for the greater probability of small deletions than small insertions.…”
Section: Small Deletions and Small Insertions: Frameshift Mutations Asupporting
confidence: 83%
“…Although most deletions/insertions cause a frameshift, amino acid deletions are found in 4.3% (16/374) of the studied patients (9/282 mutations). Ball et al detected a significantly lower frequency of in-frame 3-bp and 6-bp events (Ball et al, 2005), which would cause the deletion of one or two amino acids. The authors hypothesize that some of these in-frame lesions would probably produce a milder or null phenotype that would not be identified by clinicians.…”
Section: Small Deletions and Small Insertions: Frameshift Mutations Amentioning
confidence: 98%
“…A deletion of four nucleotides (ACTC) at position 1048-1051 in exon 10 in the SLC7A9 gene ( Figure 2C) was detected in the homozygous state, in a Turkish patient (CY-36). This mutation was most probably generated by a mechanism of "slipped misspairing" between the two direct repeats (TC), followed by a deletion of one of the direct repeats and the intervening AC sequence [14]. Because of the urinary excretion profile of the parents, the patient was classified as non type I/non type I (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The proposed independent origins of the identical duplication in at least three different FEO pedigrees suggest that the duplication occurs at a mutation hotspot and is consistent with these models. The repetitive and G/C-rich nature of the sequences surrounding the close and partly overlapping duplications of the FEO, early-onset PDB, and ESH duplications are likely to promote mutation events [15]. The preponderance of CTG repeats may be particularly important in this regard [16].…”
Section: Discussionmentioning
confidence: 99%